Characterization of nurses’ work methods: The analysis of a Portuguese hospital - João Miguel Almeida Ventura-Silva; Maria Manuela Ferreira Pereira da Silva Martins; Letícia de Lima Trindade; Ana da Conceição Alves Faria; Sónia Cristina da Costa Barros; Ricardo Manuel da Costa Melo; Olga Maria Pimenta Lopes Ribeiro (Nursing Practice Today, 2023)
Background & Aim: Providing nursing care occurs through work methods that ensure the organization and implementation of care: the functional work method, the teamwork method, the individual work method, or the reference nurse work method. This study aims to identify work methods that nurses adopt in a Portuguese hospital. Methods & Materials: A cross-sectional study was conducted in a hospital in northern Portugal. A non-probabilistic convenience sampling technique was used, and 627 nurses were enrolled. Data were collected between March and April 2023 using the “Nurses’ Work Methods Assessment Scale.” The Statistical Package for the Social Sciences was used to perform descriptive and inferential statistics, using the Mann-Whitney, Kruskal-Wallis, and Spearman’s correlation tests. Results: The individual method predominated, followed by the functional and teamwork methods. A lower adherence to the nurse reference method was observed. The variable “work context” was the most significant for the four working methods. In the individual method, the frequency of the variable “condition in which the profession is practiced” was higher in specialist nurses and, particularly, rehabilitation nursing specialists. The frequency of using the individual method is also higher when nurses have a master’s degree and training in nursing care organization methodology. Conclusion: The highest frequencies of the individual method are related to the level of training, suggesting the influence of training in adopting working methods in clinical practice. Although the reference nurse method points to better satisfaction of clients’ needs, nursing practice environments sometimes have inadequate conditions for its operationalization.